Development of Online Student Worksheets for the Topic 'My Indonesia is Rich in Culture’ in the IPAS Subject for Fourth Grade Elementary Students : Pengembangan E-LKPD berbasis kearifan lokal pada materi Indonesiaku kaya budaya bidang studi IPAS kelas IV - Amalia, Nanda Prety; Tanjungsari, Tita; Ach. Andiriyanto (Prodi Pendidikan Guru Sekolah Dasar, 2025)
Indonesian culture should be preserved through education, but in reality, cultural learning is often overlooked because it is considered outdated. To attract students' interest, learning about culture needs to keep up with technological developments. This research aims to: (1) describe the development process of an E-LKPD based on local wisdom for the topic Indonesiaku Kaya Budaya in IPAS for Grade IV students, and (2) find out students’ responses after using the E-LKPD. The research uses the 4D development model by Thiagarajan, consisting of four stages: define, design, develop, and disseminate. Feasibility results from material experts showed a percentage of 94%, and media experts gave 87.5%, both categorized as